Reverse Signaling by MHC-I Molecules in Immune and Non-Immune Cell Types - Muntjewerff, Elke M.; Meesters, Luca D.; Bogaart, Geert van den; Revelo, Natalia H. (Frontiers in Immunology, 2020)
Major histocompatibility complex (MHC) molecules are well-known for their role in antigen (cross-) presentation, thereby functioning as key players in the communication between immune cells, for example dendritic cells (DCs) and T cells, or immune cells and their targets, such as T cells and virus-infected or tumor cells. However, much less appreciated is the fact that MHC molecules can also act as signaling receptors. In this process, here referred to as reverse MHC class I (MHC-I) signaling, ligation of MHC molecules can lead to signal-transduction and cell regulatory effects in the antigen presenting cell. In the case of MHC-I, reverse signaling can have several outcomes, including apoptosis, migration, induced or reduced proliferation and cytotoxicity towards target cells. Here, we provide an overview of studies showing the signaling pathways and cell outcomes upon MHC-I stimulation in various immune and non-immune cells. Signaling molecules like RAC-alpha serine/threonine-protein kinase (Akt1), extracellular signal-regulated kinases 1/2 (ERK1/2) and nuclear factor-κB (NF-κB) were common singaling molecules activated upon MHC-I ligation in multiple cell types. For endothelial and smooth muscle cells, the in vivo relevance of reverse MHC-I signaling has been established, namely in the context of adverse effects after tissue transplantation. For other cell types, the role of reverse MHC-I signaling is less clear, since aspects like the in vivo relevance, natural MHC-I ligands and the extended downstream pathways are not fully known. The existing evidence, however, suggests that reverse MHC-I signaling is involved in the regulation of the defense against bacterial and viral infections and against malignancies. Thereby, making reverse MHC-I signaling a potential target for therapies against viral and bacterial infections, cancer immunotherapies and management of organ transplantation outcomes.